-6x(2x-4)=0

Simple and best practice solution for -6x(2x-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x(2x-4)=0 equation:



-6x(2x-4)=0
We multiply parentheses
-12x^2+24x=0
a = -12; b = 24; c = 0;
Δ = b2-4ac
Δ = 242-4·(-12)·0
Δ = 576
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{576}=24$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(24)-24}{2*-12}=\frac{-48}{-24} =+2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(24)+24}{2*-12}=\frac{0}{-24} =0 $

See similar equations:

| 3(x+1)=5x-13 | | 49=12n-11 | | 5r-8=3r+18 | | 4x+2(×+6)=36 | | -10v-6=6v+10 | | 2(3)+10y=6 | | -3(x+2)+13=14-4x | | 3x=2x+50x= | | 4m–8m–-14m–10=-20 | | 225=65+(25+7)n | | 15x=2x+65 | | 2(3x+2)=1/2(12x+8 | | 33+y=70 | | 4y-11=2y+13 | | 19y+34=91 | | 9y-15=4y+20 | | 12.9x+70*125=233*70 | | 11+2x=29 | | 3x^2+72-33x=0 | | -22-x=5+6x=9 | | 5x²+10x+5=0 | | p2+13p+12=0 | | 520+x=603 | | 16x^2+19x-20=0 | | a2-3a-28=0 | | |4x+5|=|−29+-4x| | | 7x-9=12x-36 | | -3x+2-5x−7=4x+2 | | n2+8n+7=0 | | 12.9x-70*125=233*70 | | x-70=74+7x | | 2/9z=18 |

Equations solver categories